Heat-cured poly(methyl methacrylate) resin incorporated with different food preservatives as an anti-microbial denture base material - Montri Ratanajanchai; Widchaya Kanchanavasita; Kallaya Suputtamongkol; Amonrat Wonglamsam; Sirinporn Thamapipol; Ornthida Sae-Khow (Elsevier, 2021)
Background/purpose: The colonization of microorganisms onto denture bases is one common problem that can contribute to oral diseases. Herein, three food preservatives, including zinc oxide, potassium sorbate, and sodium metabisulfite were introduced as anti-microbial additives into a heat-polymerized poly(methyl methacrylate) (PMMA). Materials and methods: Relative microbial reductions of the modified PMMA resins against Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans were evaluated. The in vitro cytotoxicity of the materials was measured against mouse fibroblast L929 cells. A three-point flexural test was performed to determine a flexural strength and modulus properties of the materials. Results: The incorporation of all preservative agents into the material diminished the microbial growth of three microbial species. The PMMA resin combined with sodium metabisulfite exhibited the greatest anti-microbial activity that reduced almost all bacterial cells and about 40% of C. albicans. All modified resins showed no significant cytotoxicity against L929 cells. The addition of food preservatives did not significantly alter the flexural strength of the PMMA resin (∼84-92 MPa). However, the flexural modulus of the PMMA incorporated with food preservatives (∼2,024-2,144 MPa) was significantly lower than the unmodified PMMA. Conclusion: Three food preservatives, especially sodium metabisulfite, could be applied as anti-microbial additives into the denture base resin. The PMMA incorporated with the additives did not show cytotoxicity. Although, the addition of the food preservatives altered the mechanical properties, the materials still provided acceptable flexural properties.